Coaching knowledge, sport emotion, and perceived performance in Korean judoka - Nam, KwangWoo; Ha, JungHoon; Yoon, SangJin (Frontiers in Psychology, 2025)
IntroductionPerceived performance is associated with coaches’ expert knowledge and athletes’ sport emotion; however, the relationships among these variables have not been studied. This study aimed to investigate the structural relationships between the coaching knowledge of judo coaches and the sport emotion and perceived performance of Korean judo practitioners, or “judoka.”MethodsData from n = 249 Korean judoka were collected via questionnaire and analyzed using frequency analysis, confirmatory factor analysis, reliability analysis, correlation analysis, and structural equation modeling.ResultsCoaching knowledge significantly increased positive emotion (β = 0.554, p < 0.001) and perceived performance (β = 0.333, p < 0.001), and significantly decreased negative emotion (β = −0.356, p < 0.001). Positive emotion significantly increased perceived performance (β = 0.638, p < 0.001), whereas negative emotion did not decrease perceived performance (β = −0.029, p = 0.427).ConclusionHigh-quality coaching knowledge is associated with higher levels of athletes’ positive emotion, reduced levels of negative emotion, and enhanced perceived performance. To optimize perceived performance, coaches should further develop their coaching expertise, while athletes should actively engage in emotion regulation strategies.